Impairment of inspiratory muscle function after COVID-19 - Nagel, Christian; Olschewski, Horst; Sorichter, Stephan; Uezgoer, Gordana; Diehm, Curt; Huppert, Peter E.; Iber, Thomas; Herth, Felix; Harutyunova, Satenik; Marra, Alberto M.; Benjamin, Nicola; Salkić, Amina; et al. (Respiration, 2022)
Persistent symptoms after acute coronavirus-disease-2019 (COVID-19) are common, and there is no significant correlation with the severity of the acute disease. In long-COVID (persistent symptoms >4 weeks after acute COVID-19), respiratory symptoms are frequent, but lung function testing shows only mild changes that do not explain the symptoms. Although COVID-19 may lead to an impairment of the peripheral nervous system and skeletal muscles, respiratory muscle function has not been examined in this setting.
Gesehen am 08.11.2023